2016
DOI: 10.1038/pr.2016.156
|View full text |Cite
|
Sign up to set email alerts
|

Inotropes do not increase cardiac output or cerebral blood flow in preterm piglets

Abstract: In order to provide better cardiovascular support, it may be necessary to develop treatments that target receptors with a more mature profile than adrenoceptors in the preterm newborn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…We have previously reported that preterm piglets have lower cardiac outputs and MAPs than term piglets (Eiby et al . ). This study shows that, in preterm piglets, blood volume removal leads to further reductions in cardiac output, MAP and cerebral blood flow.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…We have previously reported that preterm piglets have lower cardiac outputs and MAPs than term piglets (Eiby et al . ). This study shows that, in preterm piglets, blood volume removal leads to further reductions in cardiac output, MAP and cerebral blood flow.…”
Section: Discussionmentioning
confidence: 97%
“…The piglets included in this study are a subset of the animals in which we described the response to dopamine and dobutamine under baseline conditions (Eiby et al . ). Piglets were delivered by Caesarean section at either 97 days (preterm; developmentally similar to a human neonate at 27 weeks’ gestation) or 113 days (term) where full term is 115 days (Eiby et al .…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations